PELANGGARAN ETIKA PARIWARA INDONESIA PADA IKLAN PODCAST LENTERA MALAM DAN BESOK PAGI SPOTIFY NON PREMIUM - Fajrin, Muhammad; Framanahadi, Framanahadi; Nugroho, Irawan Aditya; Junaedi, Fajar (Jurnal Bincang Komunikasi, 2024)
Advertising cannot be separated from the legal order agreed upon by all parties, in this case the Indonesian Advertising Ethics plays an important role in advertising references. This research describes the Indonesian Advertising Ethics Violations in the non-premium Spotify Night Lentera and Tomorrow Morning Advertisements through a qualitative descriptive approach to answer the problem statement. The qualitative descriptive approach is a scientific research method that aims to obtain an in-depth understanding of a particular phenomenon, event or problem. As advertising is regulated by Indonesian advertising ethics, it was found that there was a discrepancy between the content of the advertisement and the EPI guidelines, researchers found frightening narratives that were concretely violated by users of Lentera Malam and Besok Pagi. It is written in one of the articles in the EPI that advertising must not cause or play on fear.